The online application of binding condition B in native and non-native pronoun resolution - Patterson, Clare; Trompelt, Helena; Felser, Claudia (Frontiers in Psychology, 2014)
Previous research has shown that anaphor resolution in a non-native language may be more vulnerable to interference from structurally inappropriate antecedents compared to native anaphor resolution. To test whether previous findings on reflexive anaphors generalise to non-reflexive pronouns, we carried out an eye-movement monitoring study investigating the application of binding condition B during native and non-native sentence processing. In two online reading experiments we examined when during processing local and/or non-local antecedents for pronouns were considered in different types of syntactic environment. Our results demonstrate that both native English speakers and native German-speaking learners of English showed online sensitivity to binding condition B in that they did not consider syntactically inappropriate antecedents. For pronouns thought to be exempt from condition B (so-called 'short-distance pronouns'), the native readers showed a weak preference for the local antecedent during processing. The non-native readers, on the other hand, showed a preference for the matrix subject even where local coreference was permitted, and despite demonstrating awareness of short-distance pronouns' referential ambiguity in a complementary offline task. This indicates that non-native comprehenders are less sensitive during processing to structural cues that render pronouns exempt from condition B, and prefer to link a pronoun to a salient subject antecedent instead.